Caudal Regression Syndrome : A Case Report (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2017)
Caudal Regression Syndrome (CRS) is a spectrum of congenital malformations, which consist of anomalies of the rectum, the urinary and genital systems, the lumbosacral spine, and the lower limbs. Though exact cause that leads to caudal regression syndrome is still unknown but it is believed that genetic influence as well as maternal pathologic factor related to carbohydrate metabolism plays an important role. The severity of morphologic disorder depends on residual spinal cord function. Infant may present with mild to severe neurological involvement with or without visceral anomaly. Here, we report a case of caudal regression syndrome in an 18 months old girl and presented with hypoplastic lower limb and bladder incontinence.Chatt Maa Shi Hosp Med Coll J; Vol.15 (2); Jul 2016; Page 57-60